Relationship between Uveitis and Thyroid Disease: A 13-Year Nationwide Population-based Cohort Study in Taiwan. (17th November 2021) - Lin, Chun-Ju; Tien, Peng-Tai; Chang, Cheng-Hsien; Hsia, Ning-Yi; Yang, Yu-Cih; Lai, Chun-Ting; Bair, Henry; Chen, Huan-Sheng; Tsai, Yi-Yu
ABSTRACT: Purpose : To investigate whether patients with thyroid disease are at increased risk of uveitis. Methods : Data was collected from the Taiwan National Health Insurance system and included patients newly diagnosed with thyroid disease from 2000 to 2012. The endpoint of interest was a diagnosis of uveitis. Results : In analyzing 21, 396 patients with thyroid disease, yielding 85, 584 matched comparisons, patients with thyroid disease to have a significantly higher cumulative incidence of uveitis when compared to the control cohort with the Kaplan-Meier analysis. This result was further confirmed by Cox regression analysis. The increased risk was persistent in both genders. The association between thyroid disease and uveitis was stronger in patients without diabetes or hypertension. Conclusion : Patients with thyroid disease were found to have a higher risk for uveitis. For certain age groups or patients without diabetes or hypertension, the role of thyroid disease might be more crucial for uveitis development.